KAJIAN STRATEGI PENINGKATAN KUALITAS PRODUK INDUSTRI SAYURAN SEGAR (STUDI KASUS DI SEBUAH AGROINDUSTRI SAYURAN SEGAR) [Strategy on Product Quality Improvement of Fresh Vegetables Agroindustry: Case Study in a Fresh Vegetables Agroindustry at Bogor] - . Marimin; Heti Muspitawati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
This paper discusses strategy formulation for improving the quality of fresh vegetables agroindustry. The quality improvement strategy was formulated based on the customer expectation, key attribute process control and the comparison of internal-external factors evaluation. The customer expectations were translated using Quality Function Deployment (QFD) and pairwise comparison. Process control was used to see wheather the key process attribute (temperature for packaging room and warehouse) in capable range. The improvement strategies were formulated using SWOT analysis. The formulated strategies suggested be operated by the fresh vegetables agroindustry are fullfiling customer expectation through improvement of material handling process, packaging, warehouse and food safety assurance especially free from peptiside residue. The company should do market research to recognize the change of customer expectation and HACCP (Hazard Analysis Critical Control Point) implementation to support more operational strategy formulation.